Cooperative learning : review of research and practice - Gillies, Robyn (The Australian journal of teacher education, 2016)
Cooperative learning is widely recognised as a pedagogical practice that promotes socialisation and learning among students from pre-school through to tertiary level and across different subject domains. It involves students working together to achieve common goals or complete group tasks - goals and tasks that they would be unable to complete by themselves. This paper reviews developments in research and practice on cooperative learning and to examine the factors that help to explain its success. In particular, the review focuses on the key elements that contribute to its success and the role teachers' play in developing students' thinking and learning when implementing this pedagogical practice in their classrooms. [Author abstract]